2018
DOI: 10.1002/jsfa.9242
|View full text |Cite
|
Sign up to set email alerts
|

Engineered GH11 xylanases from Orpinomyces sp. PC‐2 improve techno‐functional properties of bread dough

Abstract: The recombinant xylanases showed potential for application in bakery processing and can improve techno-functional properties in sponges. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…In recent studies, Mesoflavibacter zeaxanthinifaciens was used to extract glutaminase-free ʟ-asparaginase enzyme that was involved in asparagine hydrolysis and played a significant role in cancer cells (Lee et al, 2016). Another study also showed its employment in the extraction of the xylanase enzyme (Oh et al, 2011) that is highly demanding in the bakery industry (Passarinho et al, 2018). Mesoflavibacter zeaxanthinifaciens is one of the essential bacteria that produce antibacterial compound during rapid and efficient screening method (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, Mesoflavibacter zeaxanthinifaciens was used to extract glutaminase-free ʟ-asparaginase enzyme that was involved in asparagine hydrolysis and played a significant role in cancer cells (Lee et al, 2016). Another study also showed its employment in the extraction of the xylanase enzyme (Oh et al, 2011) that is highly demanding in the bakery industry (Passarinho et al, 2018). Mesoflavibacter zeaxanthinifaciens is one of the essential bacteria that produce antibacterial compound during rapid and efficient screening method (Zhao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In studies on the characterization of Orpinomyces sp, its properties such as acetyl xylan esterase enzyme, optimum pH, temperature and molecular weight were determined (Blumm et al, 1999;Razeq et al, 2011).The enzyme xylanase is actively used in the production of biofuels and different industrial fields, and Orpinomyces sp. studies on the production of thermo-stable form have been reported (Passarinho et al,2019;Ventorim et al, 2018). 1.4.3.…”
Section: Carbohydrate Active Enzymes System In Neocallimastix Spmentioning
confidence: 99%
“…Xylanase treatment improves the quality of bread as it reduces the staling rate and increases the shelf-life ( Liu et al, 2017 ; Passarinho et al, 2019 ). Staling causes significant financial loss to the baking industry.…”
Section: Applications Of Extremophilic Xylanasesmentioning
confidence: 99%